Crystallization of porcine pancreatic elastase and a preliminary neutron diffraction experiment - Kinoshita, Takayoshi (International Union of Crystallography, 2007)
Porcine pancreatic elastase (PPE) resembles the attractive drug target leukocyte elastase, which has been implicated in a number of inflammatory disorders. In order to investigate the structural characteristics of a covalent inhibitor bound to PPE, including H atoms and the hydration by water, a single crystal of PPE for neutron diffraction study was grown in D(2)O containing 0.2 M sodium sulfate (pD 5.0) using the sitting-drop vapour-diffusion method. The crystal was grown to a size of 1.6 mm(3) by repeated macroseeding. Neutron diffraction data were collected at room temperature using a BIX-3 diffractometer at the JRR-3 research reactor of the Japan Atomic Energy Agency (JAEA). The data set was integrated and scaled to 2.3 Å resolution in space group P2(1)2(1)2(1), with unit-cell parameters a = 51.2, b = 57.8, c = 75.6 Å.